2000
DOI: 10.1051/analusis:2000162
|View full text |Cite
|
Sign up to set email alerts
|

Individual, species and geographic origin influence on cooperage oak extractible content (Quercus robur L. and Quercus petraea Liebl.)

Abstract: Abstract. Dry extract, ellagitanins, free ellagic acid, whisky-lactone, eugenol and vanillin have been quantified for a sample set of 61 pedunculate oaks (Quercus robur L.) and 72 sessile oaks (Quercus petraea Liebl.) originating from 6 different forests. Despite a very high interindividual variability, pedunculate oak shows higher level of dry extract, ellagitanins and free ellagic acid but lower level in volatil compounds compared to sessile oak. Inside a same species, differences between forests are less ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 8 publications
6
41
0
Order By: Relevance
“…In Figures 5 and 6, major results are presented for the complete stand and for slope, where sessile and pedunculate trees are in equal proportions (62 sessile and 57 pedunculate oaks). Mean ellagitannin content and the concentrations of some major ellagitannins (vescalin, roburin A, vescalagin and castalagin) in pedunculate oak (48.36 mg/g for total content, 15.78 mg/g for castalagin and 11.05 mg/g for vescalagin) are substantially higher than in sessile oak (34.41 mg/g, 11.76 mg/g and 6.36 mg/g respectively), in agreement with previous studies [5,14,16,[28][29][30].…”
Section: Species Differentiationsupporting
confidence: 92%
See 1 more Smart Citation
“…In Figures 5 and 6, major results are presented for the complete stand and for slope, where sessile and pedunculate trees are in equal proportions (62 sessile and 57 pedunculate oaks). Mean ellagitannin content and the concentrations of some major ellagitannins (vescalin, roburin A, vescalagin and castalagin) in pedunculate oak (48.36 mg/g for total content, 15.78 mg/g for castalagin and 11.05 mg/g for vescalagin) are substantially higher than in sessile oak (34.41 mg/g, 11.76 mg/g and 6.36 mg/g respectively), in agreement with previous studies [5,14,16,[28][29][30].…”
Section: Species Differentiationsupporting
confidence: 92%
“…[28,32,39]. A large set of wood samples from South-West of France has also been studied [13,14]. The major conclusion of these studies is that oak species effect on ellagitannin content largely predominates over geographic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the green wood tannin composition from Q. sessiliflora (French and Romanian oaks), Q. alba, (American oak) and Q. humboldtii, (Colombian oak), Table II Mosedale et al (1996) and FernĂĄndez de SimĂłn et al (2006) but similar to those observed by Masson et al (1995), Chatonnet andDubourdieu (1998), FernĂĄndez de SimĂłn et al (1999) and Doussot et al (2000). The ellagitannins analyzed were castalagin, grandinin, roburins A, B, C, D and E and vescalagin.…”
Section: Ellagitanninssupporting
confidence: 83%
“…Monogalloyl-glucose was only present in the wine spirit aged in chestnut barrels, as in the corresponding wood [123], although detection of this monomeric gallotannin in Quercus robur wood already made by other authors [127]. The robustness of the methods used in the isolation and quantification of the tannin fraction pointed to the conclusion that the above-mentioned effect could be caused by the wood intraspecific variability [145]. Concentration in mg/L gallic acid; mean values (n = 9); nd-not detected.…”
Section: Phenolic Compositionmentioning
confidence: 99%